The Impact Of Work Motivation And Religiosity On Faculty Member Performance: The Mediating Role Of Meaningful Life - Olfien Wilsyie Riruma; Lidia Sandra (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
This research aims to explore the influence of work motivation and religiosity on faculty performance, underscoring the central role of meaningful life as a mediator. A comprehensive quantitative analysis was conducted on data collected from 250 faculty members in varied academic environments from Java, Bali, and Sulawesi. The study reveals that both work motivation and religiosity have a significant impact on faculty performance. The meaning of life emerged as a partial mediator in this relationship. This indicates that the enhancement of faculty performance is also heavily contingent on how faculty members derive a sense of purpose and fulfillment from their professional roles and religious beliefs. This aspect is further mediated by the individual's ability to construct a meaningful life from their daily activities. These findings provide fresh insights into the complex interplay between personal values and professional outcomes, highlighting the necessity of fostering work environments that support the realization of meaningful experiences for each faculty member. The study significantly contributes to the existing literature by demonstrating the vital importance of meaningful life in understanding and improving faculty performance.